PT. Smart Finance's Design Of Green Budgets - Natania Kristi Keru; Frety Maong; Febrina Graca Peruge (Universitas 17 Agustus 1945 Semarang, 2023)
This century has seen an increase in the development of sustainable development, and to help with this, the green economy strategy has been established. Businesses who are aware of this are beginning to include environmental management components to the strategic roadmap in order to accommodate this programme, which needs funding in order to be carried out. As a result, many institutions are now beginning to use green budgeting techniques. A budgeting model known as